EFFECT OF COLD AND HOT ALCOHOLIC EXTRACT OF CORIANDRUM SATIVUM L SEEDS AGAINST PSEUDOMONAS AERUGINOSA AND STAPHYLOCOCCUS AUREUS - Asseel M.M. Habh; Baan Munim Twaij; Rasha Mohamed Sajet Al-Oqaili (Scholar Express Journals, 2023)
Coriandrum sativum L. (C. sativum) is one of the most important medicinal herbal extracts. Therefore, the current study included testing the inhibitory efficacy of hydroalcoholic and cold-hot alcoholic extracts of C. sativum L. seeds as an antimicrobial compared with ceftazidime (CAZ) against the growth of Pseudomonas aeruginosa and Staphylococcus aureus. The results showed that the cold alcoholic extract had antimicrobial activity against Pseudomonas aeruginosa such as ceftazidime, where the diameter of the inhibition zone reached 20 mm, while the hot aqueous extract did not show any antimicrobial effects. The mixture of cold alcoholic extract and ceftazidime was increased towards Pseudomonas aeruginosa and the inhibition zone was 29 mm in diameter. In conclusion, the alcoholic extract was shown to be the best and the efficacy of the extract also increased when combined with ceftazidime as an antimicrobial compared to the hot aqueous extract.
Keywords: Coriandrum sativum L; ceftazidime; Pseudomonas aeruginosa; Staphylococcus aureus